2023
DOI: 10.1145/3611656
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Robot-mediated Play: Forming Friendships and Expressing Identity

Abstract: Tele-operated collaborative robots are used by many children for academic learning. However, as child-directed play is important for social-emotional learning, it is also important to understand how robots can facilitate play. In this paper, we present findings from analysis of a national, multi-year case study, where we explore how 53 children in grades K-12 ( n =53) used robots for self-directed play activities. The contributions of this paper are as follows. First, we present empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…A positive correlation has been established in as many as 8 studies (e.g. Kim et al, 2023;Yueh et al, 2020;van Straten et al, 2023;Serholt et al, 2021;Konijn & Hoorn, 2020;Osawa et al, 2022;Zhexenova et al, 2020;Ahumada-Newhart et al, 2023). A noteworthy discovery by Serholt (2019) was that students who had experience with robots exhibited greater critical attitudes toward the concept of emotion recognition in robots compared to their peers without such experience.…”
Section: Figure 3 Overview Of Confirmed Relationships Between Researc...mentioning
confidence: 92%
See 2 more Smart Citations
“…A positive correlation has been established in as many as 8 studies (e.g. Kim et al, 2023;Yueh et al, 2020;van Straten et al, 2023;Serholt et al, 2021;Konijn & Hoorn, 2020;Osawa et al, 2022;Zhexenova et al, 2020;Ahumada-Newhart et al, 2023). A noteworthy discovery by Serholt (2019) was that students who had experience with robots exhibited greater critical attitudes toward the concept of emotion recognition in robots compared to their peers without such experience.…”
Section: Figure 3 Overview Of Confirmed Relationships Between Researc...mentioning
confidence: 92%
“…Konijn & Hoorn (2020) showed that the results from the standard school test indicated that pupils significantly improved their performance after learning with assistance of social robots. Ahumada-Newhart et al (2023) showed that children who feel a high chance of success at operating their robots in the remote school environment and place a high value on self-directed play activities are able to use their robots to support general friendships and also engage in play activities that contribute to self-expression and identity. Findings of the study conducted by Zhexenova et al (2020) reported that children gained similar knowledge after learning with a social robot as after learning with a teacher or with the help of a tablet.…”
Section: Figure 3 Overview Of Confirmed Relationships Between Researc...mentioning
confidence: 99%
See 1 more Smart Citation